Psychometric Properties of the Lithuanian Food Addiction Scale YFAS 2.0 - Jočbalytė, Karolina; Stanikūnas, Rytis (Psichologija, 2025)
Food addiction is uncontrolled eating which causes emotional and physical difficulties or impairments in important areas of life. This kind of eating resembles other substance use disorders in its behavioral expression and neurobiological mechanisms. In foreign countries, the most popular tool for assessing this problem is the Yale Food Addiction Scale 2.0 (abbreviated as YFAS 2.0) based on the diagnostic criteria for substance use disorder in DSM-5. This study aimed to test the structure of the Lithuanian version of the YFAS 2.0 version and evaluate its psychometric parameters. 383 subjects (65% female) participated in the survey. The study revealed that the Lithuanian version of the YFAS 2.0 scale demonstrated excellent internal consistency. Confirmatory factor analysis (CFA) for one-factor and two-factor models confirmed the original one-factor structure. 8.3% of the participants reached the diagnostic threshold for food addiction, according to the YFAS 2.0 results. In addition, YFAS 2.0 scores were positively correlated with the body mass index (BMI) and a poorer diet quality as measured by the Short Dietary Fat and Sugar Questionnaire (DFS). Thus, it has been established that the Lithuanian YFAS 2.0 version has good psychometric properties and can be applied in food addiction research.